Pseudoaneurysm of the subclavian artery following clavicle fracture due to blunt traumatism: a case report - Belmir, Hicham (Pan Afr Med J, 2020)
The clavicle fractures are frequent, vascular injuries associated with closed fractures of clavicle are rare. The pseudoaneurysms of the subclavian artery constitute an exceptional complication. We report a case of a 40-year-old who presented an expanding hematoma of the right side of the neck after a road traffic accident. Radiography of the right shoulder showed a midclavicular fracture. An arterial doppler of vessels showed a circulating hematoma in the contact of the right subclavian artery with a correct distality flow. Computed tomographic angiogram of the chest confirmed the diagnosis of a false aneurysm in the postvertebral portion of the right subclavian artery. The treatment was surgical and consisted of excision of the false aneurysm and a repair of the arterial injury by an arterial patch, the clavicle was fixed with a reconstruction plate and screws. Early intervention appears to be indicated due to the risk of thrombo-embolic complications. Endovascular repair appears to be the preferred treatment modalities, due to a lower rate of cardiopulmonary complications, but it is reserved for much selected cases.